Shotgun Metagenome Analysis of Two Schizaphis graminum Biotypes over Time With and Without Carried Cereal Yellow Dwarf Virus - Yan M. Crane; Charles F. Crane; Subhashree Subramanyam; Brandon J. Schemerhorn (Insects, 2025)
The greenbug aphid (Schizaphis graminum (Rondani)) is a major pest of wheat and an important vector of wheat viruses. An RNA-seq study was conducted to investigate the microbial effects of two greenbug genotypes, the presence or absence of cereal yellow dwarf virus, and the condition of the wheat host over a 20-day time course of unrestricted greenbug feeding. Messenger RNA reads were mapped to ca. 47,000 bacterial, 1218 archaeal, 14,165 viral, 571 fungal, and 94 protozoan reference or representative genomes, plus greenbug itself and its wheat host. Taxon counts were analyzed with QIIME2 and DESeq2. Distinct early (days 1 through 10) and late (days 15 and 20) communities differed in the abundance of typical enteric genera (Shigella, Escherichia, Citrobacter), which declined in the late community, while the ratio of microbial to greenbug read counts declined 50% and diversity measures increased. The nearly universal aphid endosymbiont, Buchnera aphidicola, accounted for less than 25% of the read counts in both communities. There were 302 differentially expressed (populated) genera with respect to early and late dates, while 25 genera differed between the greenbug genotypes and nine differed between carrier and virus-free greenbugs. The late community was likely responding to starvation as the wheat host succumbed to aphid feeding. Our results add to basic knowledge about aphid microbiomes and offer an attractive alternative method to assess insect microbiomes.